Phthalimide analogs for antimalarial drug discovery. Issue 11 (14th September 2021) - Bansal, Meenakshi; Upadhyay, Charu; Poonam; Kumar, Sumit; Rathi, Brijesh
Abstract : Potent phthalimide-based antiplasmodial compounds are active at different stages of the Plasmodium falciparum life cycle. Abstract : Malaria remains one of the world's most life-threatening diseases and, thus, it is a major public health concern all around the world. The disease can become devastating if not treated with proper medication in a timely manner. Currently, the number of viable treatment therapies is in continuous decline due to compromised effectiveness, probably owing to the complex life cycle of Plasmodium falciparum. The factors responsible for the unclear status of malaria eradication programmes include ever-developing parasite resistance to the most effective treatments used on the frontline ( i.e., artemisinin derivatives) and the paucity of new effective therapeutics. Due to these circumstances, the development of novel effective drug candidates with unique modes of action is essential for overcoming the listed obstacles. As such, the discovery of novel chemical compounds based on validated pharmacophores remains an unmet need in the field of medicinal chemistry. In this area, functionalized phthalimide (Pht) analogs have been explored as potential candidates against various diseases, including malaria. Pht presents a promising bioactive scaffold that can be easily functionalized and thus utilized as a starting point for the development of new antimalarial candidates suitable for preclinical and clinical studies. In this short review, we highlight a wide range of Pht analogs that have been investigated for their activity against various strains of Plasmodium falciparum .